Nanomechanical DNA Origami pH Sensors - Kuzuya, Akinori (Sensors (Basel), 2014)
Single-molecule pH sensors have been developed by utilizing molecular imaging of pH-responsive shape transition of nanomechanical DNA origami devices with atomic force microscopy (AFM). Short DNA fragments that can form i-motifs were introduced to nanomechanical DNA origami devices with pliers-like shape (DNA Origami Pliers), which consist of two levers of 170-nm long and 20-nm wide connected at a Holliday-junction fulcrum. DNA Origami Pliers can be observed as in three distinct forms; cross, antiparallel and parallel forms, and cross form is the dominant species when no additional interaction is introduced to DNA Origami Pliers. Introduction of nine pairs of 12-mer sequence (5′-AACCCCAACCCC-3′), which dimerize into i-motif quadruplexes upon protonation of cytosine, drives transition of DNA Origami Pliers from open cross form into closed parallel form under acidic conditions. Such pH-dependent transition was clearly imaged on mica in molecular resolution by AFM, showing potential application of the system to single-molecular pH sensors.